Do Where People Interact Matters to Social Capital? Comparative Analysis of Middle- and High-Rise Public Housing - Malik, Alpraditia (Journal of Architectural Design and Urbanism, 2023)
As a growing country, the challenge of providing affordable housing has grown over recent years. Public housing has emerged as a leading government initiative to provide better housing alternatives, especially for low incomes. However, due to the limited land availability, public housing development has shifted from middle- to high-rise housing type. Previous studies have shown that high-rise living can have detrimental effects on low-income residents, especially regarding their social capital. This study explores the interactional spaces within both housing types, their social capital, and whether the former influences the latter. Quantitative analysis was conducted on 255 respondents in middle- and high-rise public housing for low incomes in the Jakarta Special Region, Indonesia. The results indicated some similarities as well as differences in both housing styles. Respondents in both housing types mostly interacted in corridor areas, even though the percentage was higher for the high-rise case. Moreover, while both cases lacked the same social capital indicators, the middle-rise case had a relatively better situation than its high-rise counterparts. Furthermore, it was found that interactional spaces appear to influence their social capital, and the effects were varied for both middle- and high-rise and each social capital indicator. This study concludes that the intensity of interaction within a particular space does not necessarily translate to better social capital.